Lmx1b Influences Correct Post-mitotic Coding of Mesodiencephalic Dopaminergic Neurons - Wever, Iris; Largo-Barrientos, Pablo; Hoekstra, Elisa J.; Smidt, Marten P. (Frontiers in Molecular Neuroscience, 2019)
The Lim Homeobox transcription factor 1 beta (LMX1b) has been identified as one of the transcription factors important for the development of mesodiencephalic dopaminergic (mdDA) neurons. During early development, Lmx1b is essential for induction and maintenance of the Isthmic Organizer (IsO), and genetic ablation results in the disruption of inductive activity from the IsO and loss of properly differentiated mdDA neurons. To study the downstream targets of Lmx1b without affecting the IsO, we generated a conditional model in which Lmx1b was selectively deleted in Pitx3 expressing cells from embryonic day (E)13 onward. Supporting previous data, no significant changes could be observed in general dopamine (DA) marks, like Th, Pitx3 and Vmat2 at E14.5. However, in depth analysis by means of RNA-sequencing revealed that Lmx1b is important for the mRNA expression level of survival factors En1 and En2 and for the repression of mdDA subset mark Ahd2 during (late) development. Interestingly, the regulation of Ahd2 by Lmx1b was found to be Pitx3 independent, since Pitx3 mRNA levels were not altered in Lmx1b conditional knock-outs (cKO) and Ahd2 expression was also up-regulated in Lmx1b/Pitx3 double mutants compared to Pitx3 mutants. Further analysis of Lmx1b cKOs showed that post-mitotic deletion of Lmx1b additional leads to a loss of TH+ cells at 3 months age both in the VTA and SNc. Remarkably, different cell types were affected in the SNc and the VTA. While TH+AHD2+ cells were lost the SNc, TH+AHD2- neurons were affected in the VTA, reflected by a loss of Cck expression, indicating that Lmx1b is important for the survival of a sub-group of mdDA neurons.